Existence of multiple solutions for a class of nonhomogeneous problems with critical growth - Mohammed Massar (Electronic Journal of Qualitative Theory of Differential Equations, 2017)
In this paper, we study the existence and multiplicity of solutions for $(p_1(x),p_2(x))$-equation with critical growth. The technical approach is mainly based on the variational method combined with the genus theory.